Pulse Consumption among Portuguese Adults: Potential Drivers and Barriers towards a Sustainable Diet - Duarte, M (2020)
The transition from diets rich in animal products to plant-based protein foods—like pulses—is crucial, for both environmental sustainability and human health. The aim of this study was to characterize the current consumption and to describe the drivers of and barriers to pulse intake in Portugal. Using a quantitative approach, a semi-structured questionnaire was distributed online, and 1174 valid responses were obtained. The most consumed pulses were beans and peas, consumed at least once a week by 48.3% and 44.4% of the sample, respectively. When participants were asked about the possibility of replacement, even partially, of animal products for pulses, 15.0% stated they would not substitute even in a food scarcity scenario. In the qualitative study, ten individuals involved at different steps of pulses’ supply and value chain were interviewed in order to study individual behaviors and experiences linked knowledge and consumption of pulses. It was noticed that the lack of recognition of their nutritional value, the high cooking time and the effect of the anti-nutritional factors were commonly pointed out as barriers. The identification and understanding of perceived barriers for that low consumption will leverage the development of new strategies to promote this promising alternative.